Analysis of problems occurring in the care of a patient with liver cirrhosis - Czerwińska Pawluk, Iwona; Kowalska, Bożena; Zukow, Walery (Journal of Education, Health and Sport, 2024)
Introduction: Liver cirrhosis is a disease whose development is influenced by many factors, including those related to lifestyle. The disease causes disturbances in the functioning of not only the liver but also many other organs and systems. During the course of the disease, there are a number of complications that affect the patient’s functioning in all areas. Patients with liver cirrhosis require constant and systematic treatment and comprehensive care, including care provided by nursing staff. Purpose of research: Analysis of problems occurring in the care of patients with liver cirrhosis Material and methods: The study included 103 patients with liver cirrhosis, hospitalized from October 10, 2022 to April 10, 2023. in the Observation and Infection Ward for Adults of the SPZOZ in Puławy. The method used in the work was a diagnostic survey, the technique was a survey, and the research tool was an original survey questionnaire developed for the needs of the research. Results: Patients with liver cirrhosis have many problems of a physical nature and related to non-compliance with medical recommendations, which may affect the inhibition of the progression of the disease, the prevention of complications and the improvement of the general condition. Conclusions: Patients with liver cirrhosis have a number of physical problems, the knowledge of which may affect the organization of work of nursing staff, facilitate the identification of problems, help determine the goal of care and plan nursing interventions. Not all respondents followed the specialist’s recommendations, including: in the field of pharmacotherapy, dietary recommendations, performing check-ups, reporting for follow-up visits and physical activity. An important element in the care of a patient with liver cirrhosis is patient education and motivation to follow recommendations that are important in stopping the progression of the disease, preventing complications and improving the general condition.